Pengembangan Model Pembelajaran Kooperatif Berbasis Literasi Berkarakter dengan Game Who Am I - Prihatmojo, Agung; Rohmani, Rohmani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The development of a cooperative learning model based on literacy character with the game Who am I aims to improve literacy activities, and student learning outcomes in elementary school. This research method is Research and Development (R&D). The approach used in research is Research & Development. This research uses descriptive qualitative data analysis techniques. The sample in this study was grade V students of Soekarno Hatta Elementary School who numbered 10 students. Data collection is done by observation, interviewing and data collection related to learning models so as to get information as a cooperative learning model development planning. A cooperative model based on literacy character with the Who am I game that has been tested limited shows literacy activities run 100%, students are active in Q&A activities in the game, and learning results show all students complete with an average learning outcome of 80.3. In conclusion, the cooperative learning model based on literacy in the character of the game Who am I is effective in improving the literacy activities of grade V students at SD Soekarno Hatta, is seen from the improvement of learning outcomes and assessment. Keywords: Game Who am I, Literacy, Cooperative Learning